Case Report: The window that closed too soon: lessons from a late CLN2 diagnosis and death of a 9-year-old boy - Anna Bryzik; Dawid Larysz; Patrycja Larysz; Julia Izabela Karpierz; Justyna Paprocka (Frontiers in Genetics)
A class of progressive, autosomal recessive neurodegenerative diseases known as neuronal ceroid lipofuscinoses (NCLs) are brought on by lysosomal protein or enzyme dysfunction. This leads to the pathological buildup of autofluorescent ceroid-lipofuscin in neurons and other tissues. In children and young adults, NCLs are the most frequent cause of dementia and neurodegeneration, and epilepsy, psychomotor regression, visual decline, ataxia, and early death are all examples of clinical characteristics which may appear in the disease’s natural course. Cerliponase alfa (known as Brineura) is an enzyme replacement therapy and has become increasingly important in treating CLN2 disease (late-infantile NCL), which is caused by a deficiency of the lysosomal enzyme tripeptidyl peptidase 1 (TPP1). When started early, it can significantly slow the progression of the disease. We describe the course of a boy’s diagnosis and treatment of CLN2 disease, which demonstrates the negative effects of delayed recognition. NCL was not suspected until more than a year after treatment-resistant epilepsy, progressive ataxia, and psychomotor decline appeared, despite early-onset speech delay, developmental variability, and epileptic seizures beginning at age 3. Clear abnormalities were not found by initial imaging or genetic testing. The child’s neurological decline was already severe by the time biochemical and molecular confirmation of CLN2 disease was obtained at the age of 5, and with increasing seizures, loss of motor and cognitive abilities, vision loss, gastrostomy, tracheostomy, and death at 9 years, he progressed according to the natural course of CLN2. Even with repeated medical contact and neurological evaluations, this case highlights the difficulty of diagnosing NCLs and the significant chance of missing the limited therapeutic window. It emphasizes how neurologists and pediatricians need to be more aware of NCLs as possible causes of developmental regression and early-onset epilepsy. Children with such presentations may benefit from earlier metabolic or enzyme testing, which could increase access to treatments that prolong life and change the disease’s deadly course.